2013
DOI: 10.1007/s11948-013-9450-7
|View full text |Cite
|
Sign up to set email alerts
|

From Cases to Capacity? A Critical Reflection on the Role of ‘Ethical Dilemmas’ in the Development of Dual-Use Governance

Abstract: The dual-use issue is often framed as a series of paralyzing 'dilemmas' facing the scientific community as well as institutions which support innovation. While this conceptualization of the dual-use issue can be useful in certain contexts (such as in awareness-raising and as part of educational activities directed at the scientific community) its usefulness is more limited when reflecting on the governance and politics of the dual-use issue. Within this paper, key shortcomings of the dilemma framing are outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The case of perceived risks from dual-use research illustrates the various levels on which publishing pressures can operate. In this case, participants cited both a positive and negative impact of the controversy over dual-use research on publishing results from these lines of research (Edwards, Revill & Bezuidenhout, 2014). While existing or potential publishing restrictions may have discouraged some researchers from pursuing these lines of research, the visibility (as measured both by citations and other metrics such as tweets) received by those studies may also have made them attractive to top journals.…”
Section: The Academic Reward System: Publishing and Fundingmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of perceived risks from dual-use research illustrates the various levels on which publishing pressures can operate. In this case, participants cited both a positive and negative impact of the controversy over dual-use research on publishing results from these lines of research (Edwards, Revill & Bezuidenhout, 2014). While existing or potential publishing restrictions may have discouraged some researchers from pursuing these lines of research, the visibility (as measured both by citations and other metrics such as tweets) received by those studies may also have made them attractive to top journals.…”
Section: The Academic Reward System: Publishing and Fundingmentioning
confidence: 99%
“…In the case of avian influenza, the most well-known is dual-use research, commonly associated with "gain-of-function" experiments, whereby viruses undergo mutations in a laboratory setting (for example, Herfst et al, 2012), leading to, some argue, a safety risk for the general public. Since 2011, this has been an object of intense technical, ethical and policy debate, with significant implications for the governance of research (Edwards, Revill, & Bezuidenhout, 2014;Suk, Bartels, Broberg, Struelens, & Ozin, 2014). Others hinted at control measures arising from flu research that might have an unacceptably adverse effect on livelihoods.…”
Section: Narratives Of Riskmentioning
confidence: 99%
“…Whereas the ‘ethical dilemma framing’ of DURC might be useful in specific contexts, such as education and awareness-raising, it has considerable shortcomings [ 31 ]. Firstly, the ‘ethical dilemma framing’ does not mirror the way in which the dual use issue is experienced and responded to by the scientific community.…”
Section: Main Textmentioning
confidence: 99%
“…Studies can even unravel the reason for these behaviors. Studies in the area have identified causes related to individual characteristics -personality; interpersonal-relationship with the leader or with co-workers; and organizational-failures in code of conduct and governance (EDWARDS et al, 2014;STORY, 2018). Also, several denominations are found in the literature with similar approaches: such as misbehavior (OLIVEIRA, 2015;SONG;HAN, 2017;BAMFO et al, 2018;HALL;MARTIN, 2019); ethical dilemmas (JENKINS, 2017;NESS;CONNELLY, 2017;; unethical proorganizational behavior (UPB) (UMPHRESS;et al, 2010), and even corporate crimes.…”
Section: Introductionmentioning
confidence: 99%